BiOBr/Bi24O31Br10 heterojunctions in situ prepared by microwave-assisted hydrothermal method for aerobic oxidation of glycerol to formic acid. (June 2022) - Yue, Chengguang; Lin, Yuhan; Sang, Jingting; Li, Ziyang; Zhang, Pingbo; Fan, Mingming; Leng, Yan; Jiang, Pingping; Haryono, Agus
Abstract: Aerobic oxidation of glycerol to formic acid is a promising high value-added conversion path for glycerol, which not only can avoid the waste of excess glycerol resources, but also might reduce the dependence on non-renewable petrochemical resources in the current industrial production of formic acid. In this work, novel BiOBr/Bi24 O31 Br10 heterojunctions were in situ prepared by microwave-assisted hydrothermal method. A series of characterizations showed the as-prepared catalyst having larger specific surface area, stronger light absorption capacity and more effective separation and transfer of photo-generated carriers, which owing to the short preparation process and the successful construction of type II heterojunction. BiOBr/Bi24 O31 Br10 heterojunctions can achieve efficient and stable conversion of glycerol to formic acid under alkaline conditions (the selectivity of formic acid was 63.1% when the glycerol conversion was 95.0% at pH=13). Combining EPR and radical trapping experiment, superoxide radical and singlet oxygen were confirmed to be the main active oxygen species, and photo-generated h + also played an important role in this reaction system. Graphical Abstract: ga1 Highlights: Microwave-assisted method was applied to prepare BOB-13 rapidly. BOB-13 has large specific surface area and strong light absorption capacity. The selectivity of formic acid reached 63.1% in glycerol oxidation over BOB-13.